Universal ideals in local realities: online viewing in South Korea, Brazil and India - Evans, Elizabeth; McDonald, Paul; Bae, Juyeon; Ray, Sriparna; Santos, Emanuelle (Sage, 2016)
The potential of the internet to act as a global distribution outlet for screen content has long come into conflict with the nationally-focused strategies of producers, broadcasters, governments and internet service providers. Online viewing therefore acts as a useful case study for interrogating how tensions between ‘global’ and ‘local’ manifest within an increasingly digitized media landscape. This article examines the online viewing markets in three countries at different stages of digital maturity (South Korea, Brazil, India) to consider how online viewing has evolved in each. It then examines audience questionnaire and interview data generated in each country to explore how viewers are making sense of and valuing online viewing services. By interrogating all three samples before focusing specifically on India in more detail, it examines two tensions within the global expansion of online film and television distribution: between global trends and local infrastructures, and between the ideals of online viewing services and the grounded realities of their daily use.